Ilmu Pendidikan Islam dengan Tiga Corak Bernuansa Keindonesiaan - Nadya Julia Safira; Hafidz Hafidz; Nadifa Aulia Ramadhani; Dewi Nurima Khusnul Khotimah; Akyas Zaidan Mubarak; Harist Khoirullah Al Mubarrak; Taufik Hidayat; Muhammad Ghozy ‘Aisy (STIKes Ibnu Sina Ajibarang, 2025)
Islamic education is a learning process that aims to form individuals who believe, have noble character, and contribute positively to society based on Islamic teachings. The main goal of Islamic education is to integrate spiritual, moral and intellectual values to create a generation that is worldly and spiritually superior. The Islamic education curriculum is designed to cover Islamic sciences such as the Koran, Hadith, Fiqh and Aqidah, as well as general sciences that are relevant to the needs of the times. The scope of Islamic education includes spiritual, intellectual, social and emotional aspects, which focus on the formation of a balanced human being. This article provides a comprehensive overview of the concept of Islamic education, including the meaning, objectives, curriculum, scope, uses and basics of its application, as an effort to support holistic educational development. In the challenging era of globalization, Islamic education has an increasingly strategic role. Islamic education can be a fortress for the younger generation from the negative influence of globalization, as well as a source of inspiration to create a better future. By providing strong knowledge, skills, and religious values, Islamic education can produce a young generation that is intelligent, has noble character, and is able to face future challenges.